WMD elimination lessons learned. Issue 1 (3rd March 2016) - Lugar, Richard G.
ABSTRACT: Former Senator Richard Lugar (Republican of Indiana) provided the keynote address at the workshop held in the Washington, DC, office of the James Martin Center for Nonproliferation Studies that formed the basis of this special issue of the Nonproliferation Review . In these remarks, he discussed the importance of the Cooperative Threat Reduction programs created on 1991 legislation, co-sponsored, with Senator Sam Nunn (Democrat of Georgia). Sen. Lugar called for the maintenance and continued expansion of these programs as well as for the "creative and relentless" pursuit of new opportunities to meet evolving threats from weapons of mass destruction.